1921
DOI: 10.2307/1928982
|View full text |Cite
|
Sign up to set email alerts
|

Factors Controlling the Distribution of Douglas Fir in Semi‐Arid Regions of the Northwest

Abstract: The aim of the present investigation was to obtain quantitative data on the factors which control the distribution of Douglas fir (Pseudotsuga taxifolia) in semi-arid regions of northwestern United States. It has been pointed out, as the result of observations in different localities, that Douglas fir is confined largely to north facing slopes, while south slopes are practically without forest trees except where out-cropping rocks help to furnish sufficient shelter and moisture for the establishment of seedlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1925
1925
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…The method which has been most widely used (Wiesner, 1895 and1907;Clements, 1905;Pearson, 1910;Gordon, 1912;Vouk, 1913;Grafe, 1914;Salisbury, 1916;McLean, 1917;Gail, 1921;Loftfield, 1921;Tansley, 1923;Plitt & Pessin, 1924;Pessin, 1925) is the tinting of silver chloride paper (P. 0. P.) to a standard tint and noting the time taken to reach that tint.…”
Section: Photometry In Terrestrial Habitatsmentioning
confidence: 99%
“…The method which has been most widely used (Wiesner, 1895 and1907;Clements, 1905;Pearson, 1910;Gordon, 1912;Vouk, 1913;Grafe, 1914;Salisbury, 1916;McLean, 1917;Gail, 1921;Loftfield, 1921;Tansley, 1923;Plitt & Pessin, 1924;Pessin, 1925) is the tinting of silver chloride paper (P. 0. P.) to a standard tint and noting the time taken to reach that tint.…”
Section: Photometry In Terrestrial Habitatsmentioning
confidence: 99%
“…losses. Causal factors implicated have been lower insolation (Shanks and Norris 1950, Cantlon 1953, Ayyad and Dix 1964, lower air and soil temperatures (Weaver 1917, Gail 1921, Miller 1947, Parker 1952, Cooper 1961, and higher air humidity and lower wind speeds (Weaver 1917, Gail 1921, Cottle 1932, Parker 1952 on the north-than on the south-facing slopes.…”
Section: Introductionmentioning
confidence: 99%
“…Various environmental differences have been found associated with exposure-induced differences in vegetation in the United States (Turesson 1914;Gail 1921;Shreve 1922Shreve , 1924Shreve , 1927aBates 1923;Platt 1951;Parker 1952, among others). In general, it has been found that north facing slopes may differ from adjoining south facing slopes in soil and air temperature, soil and atmospheric moisture, light intensity and wind velocity.…”
Section: Introductionmentioning
confidence: 99%